The Effect of EDTA on the Nucleation Kinetics and Mechanical Properties of KDP Crystal - Rahman, A.; Podder, J. (Journal of Scientific Research, 2012)
Potassium di-hydrogen phosphate (KDP) has been successfully grown in pure form and doped with ethylene diamine tetra acetic acid (EDTA) by low temperature solution growth technique and nucleation kinetics of KDP crystals in doped and undoped solutions were measured and analyzed. The induction period ? was measured and experiments were performed at selected degrees of supersaturation and the critical nucleation parameters like energy of formation of the critical nucleus (?G*), radius of the critical nucleus r*, nucleation rate J, number of the molecules in the critical nucleus i* have been calculated based on the classical theory of nucleation. The grown crystals have been subjected to study the mechanical property. The microhardness test was carried out on (100) plane. The load dependent hardness and work hardening coefficient was measured. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.9415 J. Sci. Res. 4 (3), 533-540 (2012)